PENGGUNAAN MEDIA BALOK BERJENJANG DALAM PEMBELAJARAN SENAM KESEIMBANGAN PADA SISWA KELAS III SD NEGERI KARANGTEJO TAHUN 2012 (Department of Physical Education, Sport, Health and Recreation, 2013)
The background of this research is the lack of students' subject matter Penjasorkes balance exercises. Lack ofstudent learning outcomes of students due to lack of spirit and also less bold in doing climbing over bridgebeams Elementary School third grade students Karangtejo District Jumo County Waterford. This study usesclassroom action research conducted through two cycles. For the observation of students' understanding of theaffective aspects of the cycle I just 81.8 criterion very well, and on the cognitive aspects of the cycle I just 65.5with the criteria pretty well, and then increased to 91.5 with the criteria very well. And affective aspects of thecycle I was only 75 but the criteria for both the second cycle increased again to 89.5 by krieria very well. secondcycle had reached 86.5 with the criteria very well. This suggests that the affective aspect of gymnastics for thebalance has increased.